Somebodys gonna get their head kicked in tonight! Aggression among young males in bars - a question of values? - Graham, Graham,Kathryn (The British journal of criminology, 2003)
Qualitative methods were used to examine aggression among young males in bars in terms the role of alcohol, social context, cultural values, rewards and punishment, and motivations for aggression. Twenty-one incidents of barroom aggression described by men aged 20-24 in semi-structured interviews were reviewed for thematic content. According to participants, alcohol played a role by making participants less aware of risks, more willing to take risks, more stimulated, more emotional and more aggressive. However, male honour, face saving, group loyalty and fighting for fun were the main motivations for barroom aggression. The most notable explanatory factor for barroom aggression among young males in the study was an overriding general acceptance and even positive endorsement of aggression in bars, suggesting that greater attention needs to be paid to the cultural values that shape the attitudes and behaviour of some young men